Antifungal action of extracts and fractions of Annona muricata L. on Candida spp. (Research, Society and Development, 2021)
Due to the wide medicinal potential of Annona muricata, research related to its applications in different areas related to health is of fundamental importance, especially with regard to infectious microorganisms with a tendency to develop resistance mechanisms, which is the case of some species of genus Candida. In this sense, the research has as main objective to verify the antifungal action of methanolic extracts of Annona muricata on Candida albicans, Candida parapsilosis, Candida krusei and Candida glabrata. The organs used to obtain methanolic extracts were the leaf and fruit of Annona muricata. For conducting the research, ATCC strains were used, which were reactivated and grown on Saboraud Dextrose Agar. The determination of the antifungal activity of the extracts was carried out using the agar diffusion technique in wells. In the analysis of the results, the measurement values ​​of the diameters of the halos indicated a more significant action in the tests carried out with the species of C. krusei and C. albicans against the raw extracts of the leaf and the fruit of A. muricata, with a halo of 30mm and 22mm respectively. In relation to the chemical fractionation carried out, the products obtained from the butanolic and hexane fractions of the leaf on strains of C. krusei, C. albicans and C. parapsilosis were the ones that presented the most significant results. Thus, it was proved that substances present in this plant can be used to control Candida strains, however, further studies are needed to identify and isolate the active biological compounds of these plants.